Sosialisasi Pemanfaatan Media Asesmen Online Berbasis Gamifikasi Bagi Kelompok Guru Komunitas Teacher Trendi - Pratiwi, Andi Citra; Daud, Firdaus; Azis, Andi Asmawati; Hamid, Muliana Gunawan; Aslam, Annisa Paramaswary (Jurusan Matematika FMIPA UNM, 2023)
The rapid development of digital technology today can provide broad opportunities for educators to carry out learning effectively and efficiently, including to improve students’ interest and to increase student engagement in learning. However, in the midst of the rapid development of digital technology, the use of digital technology for learning in various regions in Indonesia remain insignificant. There are various problems in the learning process that are often experienced by teachers, including students who are unmotivated, get bored easily, and less active during the learning process. The same thing is experienced by a group of teachers who are members of the Teacher Trendi Community. In this regard, one of the solutions is to utilize gamification-based assessment media for groups of teachers in the Teacher Trendi Community. The results of this activity show that prior to the activity, the majority of participants were already familiar with Quizizz. However, all participants remain unfamiliar with Blooket. After the implementation, there was an increase in the knowledge of teachers, teacher group in the Teacher Trendi Community regarding the use of Quizizz and Blooket as online Assessment and Gamification Tools.